ISOLATING THE FACTORS THAT CONTRIBUTE TO THE EFFECTIVENESS OF HIGH SCHOOL SCIENCE PROGRAMS. - Hanson, Robert W. (Science Education, 1962)
The article determines the characteristics of the science programs that prevailed during a three-year period in two groups of Iowa secondary schools. One group made the greatest gains in science achievement between ninth and twelfth grade. The other group mad the smallest gains in science achievement over the same three-year period. Other differences in the science programs of these two groups of schools were sought which might have contributed to the differences in pupil progress. The factors investigated, include the students, teachers, facilities and equipment, and classroom procedures and activities as reported by students.